The EU Health Union in Search of a Definition and an Open Discussion - Agnes Sipiczki; Karel Lannoo (Intereconomics, 2021)
More than other EU 'Unions', the proposed Health Union requires proper definition because the EU's competences are limited in this domain.
Keywords: 330; Gesundheitswesen; Gesundheitspolitik; Arzneimittelmarkt; EU-Staaten